(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2004)
Primary and late stages of embryogenesis of grapes Mskhali, Shahumyani, Deghin Yerevani, Parvana and Charentsi sorts were studied considering the crop capacity and the economic significance. Success of selection work is conditioned by the right choice of parental forms. The sterilization of the pollens of the mentioned sorts is the result of vegetative and generative seeds’ early degeneration in the cell of plasma. In barren sorts pollination and fecundation are possible, bit normal fertility lads, because of normal course of embryogenesis. In the result of sterilization fruits of grapes are barren and economical, it’s a normal phenomenon and grains cither don’t develop, but decay during the process of development or remain undeveloped The reason that grapes are barren can be also considered as abnormal development of reproductive organs, early destruction of female cells gametophase. In the sorts of Deghin Erevani, Parvana decay of buds takes place in the late stages of development, the result of which formed fruits can have undeveloped grains. The reason of grapes falling can be the alterations taking place in the system of female genitals.